2006
DOI: 10.7863/jum.2006.25.11.1411
|View full text |Cite
|
Sign up to set email alerts
|

Preexamination and Postexamination Assessment of Parental-Fetal Bonding in Patients Undergoing 3-/4-Dimensional Obstetric Ultrasonography

Abstract: Objective. The purpose of this study was to determine whether there is a change in parental bonding and couples' attitudes toward their fetus after undergoing 3-/4-dimensional ultrasonography (3D/4DUS). Methods. Sixty-five fathers and 124 mothers were asked to fill out a maternal-fetal attachment questionnaire relating to how they felt about their fetus before and after 3D/4DUS and to mark on a line indicating their feelings about the ultrasonography experience. In addition, 135 parents filled out a positive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 24 publications
2
36
0
2
Order By: Relevance
“…Plusieurs études ont rapporté un bénéfice significatif de l'échographie 3D dans la mise en place de la relation mère-enfant en cours de grossesse [4][5][6][7][8][9]. La plupart conclut que l'échographie 3D, grâce à la proximité de son rendu visuel avec la réalité, est plus à même de permettre le développement de cette relation.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Plusieurs études ont rapporté un bénéfice significatif de l'échographie 3D dans la mise en place de la relation mère-enfant en cours de grossesse [4][5][6][7][8][9]. La plupart conclut que l'échographie 3D, grâce à la proximité de son rendu visuel avec la réalité, est plus à même de permettre le développement de cette relation.…”
Section: Discussionunclassified
“…En dehors de toute pathologie, la proximité des images échographiques 3D avec la réalité a conduit plusieurs auteurs à s'interroger sur l'impact psychologique de cet examen et sur son bénéfice potentiel dans la mise en place de la relation mère-enfant [7][8][9][10][11][12]. Ces études rapportent toutes une mise en place plus précoce et plus intense de cette relation grâce à cette prise en charge 3D.…”
Section: Introductionunclassified
“…31 Several publications have stressed the importance of 3D/4D US in increasing maternal-fetal bonding and even helping in reducing potentially harmful behavior, such as smoking during pregnancy. 34,35 However, others have stated that when comparing 3D/4D with traditional 2D, recognition of fetal anatomy by the mothers-to-be was, indeed, improved but bonding was not better, 36,37 and there was no benefit in terms of anxiety reduction in pregnancies at risk of fetal abnormalities. 38 In addition, even assuming an improvement in maternal-fetal bonding, there are no studies showing benefits to the fetus.…”
Section: Clinical Application Of 3d/4d Ultrasound In Prenatal Diagnosismentioning
confidence: 93%
“…A number of commercial businesses in the United States have appeared in the last few years providing ultrasound services for the purpose of 'fetal photography'. Some studies have demonstrated that 3-d and 4-d ultrasound images may actually enhance maternalefetal bonding [8], yet both the United States Food and Drug Administration and the American Institute of Ultrasound in Medicine have discouraged the use of non-medical ultrasonography for entertainment purposes [9,10].…”
Section: Resource Utilizationmentioning
confidence: 99%